1998
DOI: 10.1016/s1097-2765(00)80044-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Sequence-Nonspecific Recognition of 5′-Capped mRNA by a Cap-Modifying Enzyme

Abstract: Sequence-nonspecific binding of RNA, recognition of a 7-methylguanosine 5' mRNA cap, and methylation of a nucleic acid backbone are three crucial and ubiquitous events in eukaryotic nucleic acid processing and function. These three events occur concurrently in the modification of vaccinia transcripts by the methyltransferase VP39. We report the crystal structure of a ternary complex comprising VP39, coenzyme product S-adenosylhomocysteine, and a 5' m7 G-capped, single-stranded RNA hexamer. This structure revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
194
1
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(205 citation statements)
references
References 22 publications
7
194
1
3
Order By: Relevance
“…Other non-eIF4E capbinding proteins, e.g., CBC (4) and VP39 (26), bind the cap via cation-π or π-π stacking arrangements using two aromatic residues similarly to other eIF4E family members. Indeed, there are only two examples of specific cap-binding proteins that chelate cap via a strategy different to the aromatic sandwich.…”
Section: Resultsmentioning
confidence: 99%
“…Other non-eIF4E capbinding proteins, e.g., CBC (4) and VP39 (26), bind the cap via cation-π or π-π stacking arrangements using two aromatic residues similarly to other eIF4E family members. Indeed, there are only two examples of specific cap-binding proteins that chelate cap via a strategy different to the aromatic sandwich.…”
Section: Resultsmentioning
confidence: 99%
“…The methyl group at the N7 position does not influence the 29O-MTase activity of NS5MTase DV , indicating that the enzyme does not discriminate methylated from nonmethylated RNA cap structures in the 29O-methylation step in contrast to specific viral 29O-MTases (Decroly et al, 2008;Hodel et al, 1998). The NS5MTase DV 29O-MTase activity showed steady-state parameters of both substrates and characteristics that are in agreement with other AdoMet-dependent MTases acting on polynucleotide substrates and in particular with viral 29O-MTases.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the reducing agent dithiothreitol (DTT; 5 mM) stabilized NS5MTase DV during long time-course experiments (data not shown). In all subsequent tests of NS5MTase DV on 7Me GpppAC n and GpppAC n , we used 40 mM Tris/HCl (pH 7.5) and 5 mM DTT in the absence of MgCl 2 .Interestingly, a similar bell-shaped pH curve with an optimum at 7.5 and independence from divalent cations was found for vaccinia virus mRNA cap 29O-MTase VP39 (Barbosa & Moss, 1978) containing the same catalytic tetrad, K-D-K-E (Hodel et al, 1996(Hodel et al, , 1998. Nevertheless, the optimum conditions for NS5MTase DV described here are in contrast to a reported pH optimum of 29O-MTase activity of NS5MTase DV on another type of short RNA substrate, GpppAGAACCUG, reported recently (Kroschewski et al, 2008;Lim et al, 2008).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The failure of VP39 to catalyze the 2Ј-O-methylation of capped RNAs whose cap nucleotide contains an unmethylated guanine (4), makes the enzyme particularly suitable for investigating the specific recognition of an alkylated, positively charged base. Crystallographic studies have also revealed no binding of unmethylated nucleosides and nucleotides (5,6).…”
mentioning
confidence: 99%